HUBUNGAN KETERAMPILAN MENYIMAK CERITA RAKYAT TERHADAP KETERAMPILAN MENULIS TEKS NARASI SISWA KELAS VII - yulia zani; Rasdawita; Siti Enik Mukhoiyaroh Bambang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the relationship between the listening skills of folk tales and the narrative writing skills of seventh-grade students at MTsN 6 Kota Jambi. Listening and writing are interconnected language skills, where listening as a receptive skill can strengthen writing as a productive skill. This research employed a quantitative approach with a correlational design. Data were collected using two types of tests: an objective test to assess listening skills and a performance-based test to assess narrative writing skills. Data analysis was performed using SPSS version 25. The results of the Spearman correlation test showed a correlation coefficient of 0.454 with a significance value of 0.017 (< 0.05), indicating a significant and positive relationship between listening skills in folk tales and narrative writing skills. These findings suggest that the better students' listening skills, the better their writing performance. Keywords: listening skills, writing skills, folk tales, narrative text, correlation